Comparative Analysis of Dielectric Properties of Polyvinyl Alcohol and Polyethylene - Javanbakht T. (Журнал інженерних наук)
The article presents a new comparative analysis of the dielectric properties of polyvinyl alcohol (PVA) and polyethylene (PE) at different temperatures and their other physical properties. The characteristic peaks were observed in the FTIR spectra of the polymers. The amounts of carbon and oxygen on PVA’s surface differed from PE. It was hypothesized that these properties could be affected by the increase in temperature and difference in the chemical structures of the polymers. We investigated the dielectric properties of these polymers between 20 °C and 100 °C. Our results revealed that the dielectric properties of these polymers were not the same. The actual permittivity values of PVA at low temperatures were almost constant for all frequency values and increased at higher temperatures with the decrease in frequency. The same pattern concerning the increase of imaginary permittivity of this polymer was observed at low frequencies. The increase of the real and imaginary permittivity of the PVA accompanied the increase in temperature. The actual permittivity of PE was almost constant with the frequency at different temperatures. However, the imaginary permittivity of this polymer showed an increase at low frequencies. The increase in temperature accompanies the increase of the PE’s imaginary permittivity. As expected, the capacitance, like permittivity, changed differently for the polymers. Moreover, an increase in temperature had more effect on the conductivity of PVA than that of PE. The difference in these polymers’ dielectric properties could be due to their chemical structures. The results of this article can be used for further applications of PVA and PE in science and engineering.